Implementasi Business Intelligence Untuk Analisis Data Kinerja Penjualan Menggunakan Power BI - Nur Andhini Putri; Karnadi Karnadi (Bulletin of Computer Science Research, 2025)
This study aims to apply the concept of Business Intelligence (BI) by implementing it using the Power BI tools to analyze furniture sales data. The BI approash uses technology and analytical methods to analyze, integrate, and present information needed by company. Power BI is a BI platform for interactive data visualization. This approach involves the process of collecting and integrating data, which is then presented in the form of interactive and easy-to-understand visualizations. The research methods used include a literature study related to BI concepts and technology, as well as experiment using Power BI to analyze sales data with various key performance indicators (KPIs) such as growth sales, average purchase value, profit margin, etc. the results will be interpreted to obtain valuable information for more accurate business decision making. This research is expected to provide a better understanding of the application of BI using Power BI in sales data analysis and can be used as a basis for companies in making accurate and effective business decisions to achieve company targets.